Protozoan Parasites of Rodents and Their Zoonotic Significance in Boyer-Ahmad District, Southwestern Iran - Zeinab Seifollahi; Bahador Sarkari; Mohammad Hossein Motazedian; Qasem Asgari; Mohammad Javad Ranjbar; Samaneh Abdolahi Khabisi (Veterinary Medicine International)
Backgrounds. Wild rodents are reservoirs of various zoonotic diseases, such as toxoplasmosis, babesiosis, and leishmaniasis. The current study aimed to assess the protozoan infection of rodents in Boyer-Ahmad district, southwestern Iran. Materials and Methods. A total of 52 rodents were collected from different parts of Boyer-Ahmad district, in Kohgiluyeh and Boyer-Ahmad province, using Sherman live traps. Each rodent was anesthetized with ether, according to the ethics of working with animals, and was dissected. Samples were taken from various tissues and stool samples were collected from the contents of the colon and small intestines. Moreover, 2 to 5 mL of blood was taken from each of the rodents and the sera were examined for anti-Leishmania antibodies, by ELISA, or anti-T. gondii antibodies, by modified agglutination test (MAT). DNA was extracted from brain tissue samples of each rodent and PCR was used to identify the DNA of T. gondii. Results. Of the 52 stool samples of rodents studied by parasitological methods, intestinal protozoa infection was seen in 28 cases (53.8%). From 52 rodents, 19 (36.5%) were infected with Trichomonas, 10 (19.2%) with Giardia muris, and 11 (21.2%) with Entamoeba spp. Also, 10 cases (19.2%) were infected with Blastocystis, 3 (5.8%) were infected with Chilomastix, 7 (13.5%) were infected with Endolimax, 1 (1.9%) was infected with Retortamonas, 3 (5.77%) were infected with T. gondii, and 6 (11.54%) were infected with Trypanosoma lewisi. Antibodies to T. gondii were detected in the sera of 5 (9.61%) cases. Results of the molecular study showed T. gondii infection in 3 (5.77%) of the rodents. Findings of this study showed that rodents in Kohgiluyeh and Boyer-Ahmad province, southwestern Iran, are infected with several blood and intestinal parasites; some of them might be potential risks to residents and domestic animals in the region.